Effects of the Paediatric Regulation funding on the development of off-patent medicines in children - Ruggieri, Lucia; Torretta, Silvia; Giannuzzi, Viviana; Natale, Alessandra; Felisi, Mariagrazia; Ceci, Adriana; Bonifazi, Fedele (Frontiers in Medicine, 2025)
IntroductionIn paediatrics, medicines repurposing is a particularly advantageous approach, offering a route to address unmet medical needs and turn off-label use into evidence-based treatments for paediatric populations. This study analysed the effects of funds provided under the Seventh Framework Programme for Research (FP7-FRP), issued by the European Commission from 2007 to 2013 according to the European Paediatric Regulation, in terms of new paediatric marketing authorisations (MAs) including paediatric Use Marketing Authorisations (PUMAs). Additionally, we investigated which funded projects included repurposing initiatives.MethodsData was collected on paediatric Investigation Plans (PIPs), new MAs, and MAs variations from the EMA website, national medicine registers, and final project reports. A survey to project coordinators was also conducted to explore the challenges faced during paediatric drug development plans.ResultsThe 20 FP7-funded projects studied 24 off-patent active substances. Eighteen substances had agreed PIPs with the European Medicines Agency paediatric Committee (PDCO). Positive compliance checks were granted for three PIPs, resulting in three new PUMAs. According to the adopted definition, 22 out of 24 (91.6%) paediatric development plans could be classified as repurposing. New conditions were proposed for eight substances, while 16 aimed to extend existing indications to broader paediatric populations. Additionally, 18 development plans included new age-appropriate formulations. The survey revealed that primary challenges in paediatric development plans included budgeting, lengthy regulatory processes, and recruitment.DiscussionTaken together, these results highlighted on one hand that the FP7 programme had a positive impact, as three new PUMAs were effectively obtained, representing one third of the nine PUMAs obtained since the paediatric Regulation entered into force, and three out of 18 agreed PIPs were successfully completed within 3–10 years. In addition, repurposing existing drugs for paediatric use significantly contributed to addressing unmet medical needs in paediatrics. On the other hand, the gap between the number of agreed PIPs and those that have led to PUMAs is still considerable, due to regulatory barriers and financial constraints. This underscores the need for continued support and further initiatives to streamline public-private partnerships for paediatric drug development, ensuring that off-patent medicines can be safely and effectively repurposed for paediatric use.